The Effectiveness of Interactive Digital Media in Enhancing Stu-dents’ Islamic Literacy - Suito Suito (Jurnal Multidisiplin Sahombu, 2026)
The current problem in Indonesia is the lack of literacy, which is why the development of digital technology is driving the transformation of learning methods, including in Islamic education. Students' Islamic literacy encompasses not only cognitive understanding but also the appreciation of religious values, attitudes, and practices in everyday life. This study aims to analyze the effectiveness of using interactive digital media in improving students' Islamic literacy. The research method used is a quantitative approach with a quasi-experimental design, involving an experimental group using interactive digital media and a control group using conventional learning methods. The research instruments were an Islamic literacy test and a student response questionnaire. Data analysis was conducted using descriptive and inferential statistical tests to determine differences in Islamic literacy improvement between the two groups. The results showed that the use of interactive digital media has a positive and significant impact on improving students' Islamic literacy, especially in aspects of conceptual understanding, internalization of Islamic values, and interest and motivation to learn. Interactive digital media is also able to create a more active, interesting, and contextual learning atmosphere. These findings indicate that the integration of interactive digital media in Islamic education learning is an effective strategy to improve the quality of students' Islamic literacy in the digital era.